Competence needs satisfaction in elite junior tennis: gender differences - Guinoubi, S.; Mouelhi-Guizani, S.; Chtara, M.; Crespo, M. (International Journal of Sports Science and Coaching, 2023)
Empirical studies on Basic Psychological Needs Theory in sports have increased exponentially since the turn of the millennium. Within this context, we studied the contribution of competence needs as a predictor of Reduced Sense of Accomplishment (RSA) and Balance between Challenge and Skills (BCS) in elite junior tennis players and its gender differences. A sample of 114 (62 girls and 52 boys) junior elite players (15.62 ± 1.36 years) from 24 countries competing in the International Tennis Federation world junior tournaments participated in this study. Three different questionnaires were used, Competence Needs Satisfaction (CNS) with Basic Needs Satisfaction in Sport Scale, RSA with Athlete Burnout Questionnaire, and BCS with Dispositional Flow State 2. Results showed that these scales were reliable (>.70). Independent sample t-test analysis revealed no significant gender differences in any of them (p > .05). Structural equation modeling (SEM) showed that CNS was negatively associated with RSA (r = -.46; p < .001) and positively associated with BCS (r = .81; p < .001). It can be concluded that coaches, parents, and team members should understand the relevance of adopting behaviors and programs that satisfy the competence needs of elite junior tennis players. By doing so, elite tennis players would be protected against a RSA and facilitate more confidence in aiming them to face the competitive challenges of the sport.